Microalgal remediation of anaerobic pretreated pharmaceutical wastewater for sustainable biodiesel production and electricity generation. (June 2020) - Amit,; Nayak, Jagdeep Kumar; Ghosh, Uttam Kumar
Graphical abstract: Highlights: Pretreatment of raw pharmaceutical wastewater using MFC. T. indica achieved 1.067 g L −1 biomass yield in raw wastewater. Overall reduction in COD, nitrate, phosphate and TOC were obtained as 90.29, 97.05, 81.60 and 94.87 % respectively. Abstract: Raw wastewater from final processing unit of pharmaceutical industry contains high organic loading and obstinate compounds causing treatment of this wastewater a major challenge. In this study a novel approach for the treatment of pharmaceutical wastewater has been discussed. Anaerobic pretreatment of raw pharmaceutical wastewater was done using microbial fuel cell (MFC), followed by aerobic microalgal treatment with T. indica in photobioreactor in batch mode. Combined MFC and algal treatment process showed potential reduction in heavy metals concentration along with decrease of COD, TOC, nitrate and phosphate content. The observed COD, TOC, nitrate and phosphate in raw wastewater was 90.29, 97.05, 81.60 and 94.87 %, respectively. However, after treatment of raw wastewater in photobioreactor without pretreatment, 66.30 % COD, 67.17 % nitrate, 70.03 % phosphate and 78.14 % TOC reduction were observed. T. indica achieved 16.40 and 15.69 mg L −1 d −1 of lipid productivity in PW1 and PW2 whereas it showed 0.085 and 0.089 g CO2 L −1 d -1 of CO2 Fixation rate. This study demonstrates combination treatment processes of wastewater improve environmental sustainability and enables greener routes of biofuels production.